Spodoptera Frugiperda (Fall Armyworm) Economic Impacts and Management Strategies on Maize Production in Cambodia: A Review Article - Vibol Nget; Monipheap Nem; Mardy Serey (Yayasan Adra Karima Hubbi, 2024)
Maize is a significant crop in Cambodia and is extensively grown in upland areas with higher rainfall and suitable soil conditions. The production of maize in Cambodia is being affected by the presence of fall armyworm (Spodoptera frugiperda), which can significantly reduce productivity without proper control methods. Fall armyworm (FAW) is a crop insect pest originally from America, which was later discovered in West Africa in 2016 and appeared in Cambodia in March 2019. It affected 11,142 hectares of maize in four provinces within the following four months. The most affected are smallholder farmers with limited access to information, tools, technologies, and management practices to predict, identify, and manage an infestation of FAW in their fields. Cambodia is not yet prepared to address this pest. The main deficiencies are the absence of a control strategy for FAW, the lack of resources for disseminating knowledge, such as farmer field schools and trainer training, and the lack of research on it. This review aims to identify best practices and deficiencies that Cambodian farmers should consider in controlling FAW infestation. These measures are urgently needed and can be quickly tested and expanded to mitigate the impacts of FAW on maize production. This is accomplished through academic literature from scholarly articles, government regulations, international publications, and credible news about the status of FAW worldwide, in Asian nations, and in Cambodia. When using the push-pull method, the number of larvae per plant is reduced by 82.7% to 86.7%, along with a higher yield. In Cambodia, Metarhizium anisoliae is a fungal biopesticide that effectively controls FAW, while Bacillus thuringiensis and neem oil are not effective. Since the efficacy of biopesticide is longer-term and these products are difficult to access, Cambodian farmers prefer to use synthetic insecticides to suppress FAW. Emamectin benzoate, a chemical compound, is found to be popularly used by farmers in Cambodia for controlling FAW, and its efficacy has been proven to be highly effective. There is a significant concern about the resistance of this synthetic pesticide if farmers are not properly advised. Large-scale agro-advisories can play an essential role in minimizing the incidence of FAW and helping smallholder farmers take timely precautions to reduce potential crop loss. Integrated pest management is the best strategy for managing FAW.